"Cutting Edge" Technology: an avant-garde solution of operational effectiveness or careerists nightmare?. (1st January 1999) - Savery, Lawson K.; Choy, Rita M.
Modern organisations are under constant pressure to perform better with less. Through business re-engineering processes, many tasks that used to be conducted by employees are now likely to be done by state of the art technology and the operatives made redundant. Although many organisations have achieved the objective of operating under a "lean and mean" philosophy, the utilisation of "cutting edge" technology has generated a need for a flatter organisational structure and caused some middle management positions to be made redundant. The emphasis on the use of new technology, therefore, can have a significant impact on promotional opportunities for many employees. This position paper attempts to examine the relationship between the use of "cutting edge" technologies and the impact on promotion opportunities to employees. Using new technologies to replace human operators requires careful analysis and conceptual planning. The consequence of relying solely on new technologies can have adverse influences on an organisation's overall effectiveness and performance.